An empire on trial: race, murder, and justice under British rule, 1870 - 1935 - Wiener, Martin J. (Cambridge University Press, 2009)
On the high seas -- Queensland, 1869-1889 -- Fiji, 1875-1885 -- Trinidad and the Bahamas, 1886-1897 -- India : the setting -- India : in the legal arena, 1889-1922 -- Kenya, 1905-1934 -- British Honduras, 1934